The value of Canadian agriculture: Direct, indirect, and induced economic impacts - Windfeld, Emma; Lhermie, Guillaume (Frontiers in Sustainable Food Systems, 2022)
While the value of agriculture to the Canadian economy is well established, its extensive indirect and induced value through upstream and downstream industries is not. Input-Output (I/O) analyzes are a common tool that measure the direct, indirect and induced impacts of an industry to the entire economy. We reviewed I/O analyzes that used economic multipliers to estimate the total contribution of agricultural industries to Canada's economy. Reports underwent data extraction for output, Gross Domestic Product (GDP), jobs, labor income and taxes generated. We found that when indirect and induced economic impacts are considered, the value of agricultural industries is much greater than traditional valuations indicate. Beef and canola were the two largest industries in terms of GDP and jobs, with direct impacts constituting less than half of their total impacts. Recent and thorough I/O analyzes are available for only a limited number of agricultural industries. There is a need for I/O analyzes covering key agricultural industries at the regional and national level using uniform methodology and recent data and multipliers. This information is essential to gain a systemic understanding of the true economic value of agriculture and to inform policies and investment that maximizes the potential of agricultural industries.